Multi-faceted role of melatonin in neuroprotection and amelioration of tau aggregates in alzheimer's disease - Balmik, Abhishek Ankur; Chinnathambi, Subashchandrabose (Journal of Alzheimers Disease, 2018)
Alzheimer's disease (AD) is one of the major age related neurodegenerative diseases whose pathology arises due to the presence of two distinct protein aggregates, viz., amyloid-beta plaques in extracellular matrix and tau neurofibrillary tangles in neurons. Multiple factors play a role in AD pathology, which includes familial mutations, oxidative stress, and post-translational modifications. Melatonin is an endocrine hormone, secreted during darkness, derived from tryptophan, and produced mainly by the pineal gland. It is an amphipathic molecule, which makes it suitable to cross not only blood-brain barrier, but also to enter several other subcellular compartments like mitochondria and endoplasmic reticulum. In this context, the neuroprotective effect of melatonin may be attributed to its role as an antioxidant. Melatonin's pleiotropic function as an antioxidant and neuroprotective agent has been widely studied. However, its direct effect on the aggregation of tau and amyloid-beta needs to be explored. Furthermore, an important aspect of its function is its ability to regulate the process of phosphorylation of tau by affecting the function of kinases and phosphatases. In this review, we are focusing on the pleiotropic function of melatonin on the aspect of its neuroprotective function in tau pathology, which includes antioxidant function, regulation of enzymes, including kinases and enzymes involved in free radical scavenging and mitochondrial protection.
Keywords: Alzheimer's disease; hyperphosphorylation; melatonin; mitochondria; Protein aggregation; tau protein

Baicalein suppresses repeat tau fibrillization by sequestering oligomers - Sonawane, Shweta Kishor; Balmik, Abhishek Ankur; Boral, Debjyoti; Ramasamy, Sureshkumar; Chinnathambi, Subashchandrabose (Archives of Biochemistry and Biophysics, 2019)
Alzheimer's disease (AD) is a neurodegenerative disorder caused by protein misfolding, aggregation and accumulation in the brain. A large number of molecules are being screened against these pathogenic proteins but the focus for therapeutics is shifting towards the natural compounds as aggregation inhibitors, mainly due to their minimum adverse effects. Baicalein is a natural compound belonging to the class of flavonoids isolated from the Chinese herb Scutellaria baicalensis. Here we applied fluorescence, absorbance, microscopy, MALDI-TOF spectrophotometry and other biochemical techniques to investigate the interaction between Tau and Baicalein in vitro. We found the aggregation inhibitory properties of Baicalein for the repeat Tau. Overall, the potential of Baicalein in dissolving the preformed Tau oligomers as well as mature fibrils can be of utmost importance in therapeutics for Alzheimer's disease.
Keywords: Alzheimer disease; Baicalein; Microtubule assembly; Paired helical filaments; Protein aggregation; tau protein

Effect of melatonin on tau aggregation and tau-mediated cell surface morphology - Das, Rashmi; Balmik, Abhishek Ankur; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2020)
Aggregation of Microtubule-associated protein Tau and its deposition in the form of neurofibrillary tangles (NFTs) is one of the pathological hallmarks of Alzheimer's disease (AD). Tau aggregation inhibition has been targeted in various studies including natural compounds and synthetic small molecules. Here, we have studied neurohormone- Melatonin against in vitro Tau aggregation and observed its effect on membrane topology, tubulin network and Tau phosphorylation in Neuro2A and N9 cell lines. The aggregation and conformation of Tau was determined by ThT fluorescence and CD spectroscopy respectively. The morphology of Tau aggregates in presence and absence of Melatonin was studied by transmission electron microscopy. Melatonin was found to reduce the formation of higher order oligomeric structures without affecting the overall aggregation kinetics of Tau. Melatonin also modulates and helps to maintain membrane morphology, independent on tubulin network as evidenced by FE-SEM and immunofluorescence analysis. Overall, Melatonin administration shows mild anti-aggregation and cytoprotective effects. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Alzheimer's disease; Cell surface morphology; melatonin; Paired helical filaments; tau protein; Tauopathies

EGCG impedes human Tau aggregation and interacts with Tau - Sonawane, Shweta Kishor; Chidambaram, Hariharakrishnan; Boral, Debjyoti; Gorantla, Nalini Vijay; Balmik, Abhishek Ankur; Dangi, Abha; Ramasamy, Sureshkumar; Marelli, Udaya Kiran; Chinnathambi, Subashchandrabose (Scientific Reports, 2020)
Tau aggregation and accumulation is a key event in the pathogenesis of Alzheimer's disease. Inhibition of Tau aggregation is therefore a potential therapeutic strategy to ameliorate the disease. Phytochemicals are being highlighted as potential aggregation inhibitors. Epigallocatechin-3-gallate (EGCG) is an active phytochemical of green tea that has shown its potency against various diseases including aggregation inhibition of repeat Tau. The potency of EGCG in altering the PHF assembly of full-length human Tau has not been fully explored. By various biophysical and biochemical analyses like ThS fluorescence assay, MALDI-TOF analysis and Isothermal Titration Calorimetry, we demonstrate dual effect of EGCG on aggregation inhibition and disassembly of full-length Tau and their binding affinity. The IC50 for Tau aggregation by EGCG was found to be 64.2 mu M.

HDAC6 ZnF UBP as the modifier of tau structure and function - Balmik, Abhishek Ankur; Chidambaram, Hariharakrishnan; Dangi, Abha; Marelli, Udaya Kiran; Chinnathambi, Subashchandrabose (Biochemistry, 2020)
Histone deacetylase 6 is a class H histone deacetylase primarily present in the cytoplasm and involved in the regulation of various cellular functions. It consists of two catalytic deacetylase domains and a unique zinc finger ubiquitin binding protein domain, which sets it apart from other HDACs. HDAC6 is known to regulate cellular activities by modifying the function of microtubules, HSP90, and cortactin through deacetylation. Apart from the catalytic activity of HDAC6, it interacts with other proteins through either the SE14 domain or the ZnF UBP domain to modulate their functions. Here, we have studied the role of the HDAC6 ZnF UBP domain as a modifier of Tau aggregation by its direct interaction with the polyproline region/repeat region of Tau. Interaction of HDAC6 ZnF UBP with Tau was found to reduce the propensity of Tau to self-aggregate and to disaggregate preformed aggregates in a concentration-dependent manner and also bring about the conformational changes in Tau protein. The interaction of HDAC6 ZnF UBP with Tau results in its degradation, suggesting either proteolytic activity of HDAC6 ZnF UBP or its role in enhancing autoproteolysis of Tau.

Melatonin interacts with repeat domain of Tau to mediate disaggregation of paired helical filaments - Balmik, Abhishek Ankur; Das, Rashmi; Dangi, Abha; Gorantla, Nalini Vijay; Marelli, Udaya Kiran; Chinnathambi, Subashchandrabose (Biochimica Et Biophysica Acta-General Subjects, 2020)
Tau is the major neuronal protein involved in the stabilization of microtubule assembly. In Alzheimer's disease, Tau self-assembles to form intracellular protein aggregates which are toxic to cells. Various methods have been tried and tested to restrain the aggregation of Tau. Most of the agents tested for this purpose have limitations in their effectiveness and availability to neuronal cells. We have tested melatonin, a neurohormone secreted by pineal gland and a well-known anti-oxidant, for its ability to interact with the repeat domain of Tau using ITC and NMR. In aggregation inhibition and disaggregation studies of repeat Tau, melatonin was found to modulate the aggregation propensity of repeat Tau at a concentration of 5000 mu M and was more effective in dissolving preformed aggregates rather than acting as an aggregation inhibitor. However, there were no major conformational changes in Tau in presence of melatonin as observed by CD spectroscopy. On the basis of our findings, we are proposing a mechanism by which melatonin can interact with the repeat domain of Tau and exhibit its disaggregation effect.
Keywords: Alzheimer's disease; Disaggregation; melatonin; Paired helical filaments; tau protein; Tauopathies

Melatonin reduces GSK3 beta-mediated tau phosphorylation, enhances Nrf2 nuclear translocation and anti-inflammation - Das, Rashmi; Balmik, Abhishek Ankur; Chinnathambi, Subashchandrabose (ASN Neuro, 2020)
Alzheimer's disease is a neuropathological condition with abnormal accumulation of extracellular Amyloid-beta plaques and intracellular neurofibrillary tangles of Microtubule-associated protein Tau (Tau) in the brain. In pathological conditions, Tau undergoes post-translational modifications such as hyperphosphorylation by the activity of cellular kinases, which eventually leads to protein aggregation in neurons. Melatonin is a neuro-hormone that is mainly secreted from the pineal gland and functions to modulate the cellular kinases. In our study, we have checked the neuroprotective function of Melatonin by MTT and LDH assay, where Melatonin inhibited the Tau aggregates-mediated cytotoxicity and membrane leakage in Neuro2A cells. The potency of Melatonin has also been studied for the quenching of intracellular reactive oxygen species level by DCFDA assay and caspase 3 activity. Melatonin was shown to reduce the GSK3 beta mRNA and subsequent protein level as well as the phospho-Tau level (pThr181 and pThr212-pSer214) in okadaic acid-induced Neuro2A cells, as observed by western blot and immunofluorescence assay. Further, Melatonin has increased the cellular Nrf2 level and its nuclear translocation as an oxidative stress response in Tauopathy. The Melatonin was found to induce pro- and anti-inflammatory cytokines levels in N9 microglia. The mRNA level of cellular kinases such as as-GSK3 beta, MAPK were also studied by qRT-PCR assay in Tau-exposed N9 and Neuro2A cells. The immunomodulatory effect of Melatonin was evident as it induced IL-10 and TGF-beta cytokine levels and activated MAP3K level in Tau-exposed microglia and neurons, respectively. Melatonin also downregulated the mRNA level of pro-inflammatory markers, IL-1 beta and Cyclooxygenase-2 in N9 microglia. Together, these findings suggest that Melatonin remediated the cytokine profile of Tau-exposed microglia, reduced Tau hyperphosphorylation by downregulating GSK3 beta level, and alleviated oxidative stress via Nrf2 nuclear translocation.
Keywords: Alzheimer’ Anti-inflammatory; GSK3β melatonin; microglia; neurodegeneration; Nrf2; s disease; Tau hyperphosphorylation

Phagocytosis of full-length Tau oligomers by Actin-remodeling of activated microglia - Das, Rashmi; Balmik, Abhishek Ankur; Chinnathambi, Subashchandrabose (Journal of Neuroinflammation, 2020)
Background Alzheimer's disease is associated with the accumulation of intracellular Tau tangles within neurons and extracellular amyloid-beta plaques in the brain parenchyma, which altogether results in synaptic loss and neurodegeneration. Extracellular concentrations of oligomers and aggregated proteins initiate microglial activation and convert their state of synaptic surveillance into a destructive inflammatory state. Although Tau oligomers have fleeting nature, they were shown to mediate neurotoxicity and microglial pro-inflammation. Due to the instability of oligomers, in vitro experiments become challenging, and hence, the stability of the full-length Tau oligomers is a major concern. Methods In this study, we have prepared and stabilized hTau40(WT) oligomers, which were purified by size-exclusion chromatography. The formation of the oligomers was confirmed by western blot, thioflavin-S, 8-anilinonaphthaalene-1-sulfonic acid fluorescence, and circular dichroism spectroscopy, which determine the intermolecular cross-beta sheet structure and hydrophobicity. The efficiency of N9 microglial cells to phagocytose hTau40(WT) oligomer and subsequent microglial activation was studied by immunofluorescence microscopy with apotome. The one-way ANOVA was performed for the statistical analysis of fluorometric assay and microscopic analysis. Results Full-length Tau oligomers were detected in heterogeneous globular structures ranging from 5 to 50 nm as observed by high-resolution transmission electron microscopy, which was further characterized by oligomer-specific A11 antibody. Immunocytochemistry studies for oligomer treatment were evidenced with A11(+) Iba1(high) microglia, suggesting that the phagocytosis of extracellular Tau oligomers leads to microglial activation. Also, the microglia were observed with remodeled filopodia-like actin structures upon the exposure of oligomers and aggregated Tau. Conclusion The peri-membrane polymerization of actin filament and co-localization of Iba1 relate to the microglial movements for phagocytosis. Here, these findings suggest that microglia modified actin cytoskeleton for phagocytosis and rapid clearance of Tau oligomers in Alzheimer's disease condition.
Keywords: Actin; activation; Alzheimer's disease; microglia; migration; neurodegeneration; Tau Oligomers; Tauopathy

Residue-based propensity of aggregation in the Tau amyloidogenic hexapeptides AcPHF6*and AcPHF6 - Dangi, Abha; Balmik, Abhishek Ankur; Ghorpade, Archana Kisan; Gorantla, Nalini Vijay; Sonawane, Shweta Kishor; Chinnathambi, Subashchandrabose; Marelli, Udaya Kiran (RSC Advances, 2020)
In Alzheimer's disease and related tauopathies, the aggregation of microtubule-associated protein, Tau, into fibrils occursviathe interaction of two hexapeptide motifs PHF*(275)VQIINK(280)and PHF(306)VQIVYK(311)as beta-sheets. To understand the role of the constituent amino acids of PHF and PHF* in the aggregation, a set of 12 alanine mutant peptides was synthesized by replacing each amino acid in PHF and PHF* with alanine and they were characterized by nuclear magnetic resonance (NMR) spectroscopy, circular dichroism (CD), transmission electron microscopy (TEM) and ThS/ANS fluorescence assay. Our studies show that while the aggregation was suppressed in most of the alanine mutant peptides, replacement of glutamine by alanine in both PHF and PHF* enhanced the fibrillization.

Extracellular HDAC6 ZnF UBP domain modulates the actin network and post-translational modifications of Tau - Balmik, Abhishek Ankur; Sonawane, Shweta Kishor; Chinnathambi, Subashchandrabose (Cell Communication and Signaling, 2021)
Background: Microtubule-associated protein Tau undergoes aggregation in Alzheimer`s disease (AD) and a group of other related diseases collectively known as Tauopathies. In AD, Tau forms aggregates, which are deposited intracellularly as neurofibrillary tangles. Histone deacetylase-6 (HDAC6) plays an important role in aggresome formation, where it recruits polyubiquitinated aggregates to the motor protein dynein. Methods: Here, we have studied the effects of HDAC6 ZnF UBP on Tau phosphorylation, ApoE localization, GSK-3 beta regulation and cytoskeletal organization in neuronal cells by immunocytochemical analysis. This analysis reveals that the cell exposure to the UBP-type zinc finger domain of HDAC6 (HDAC6 ZnF UBP) can modulate Tau phosphorylation and actin cytoskeleton organization. Results: HDAC6 ZnF UBP treatment to cells did not affect their viability and resulted in enhanced neurite extension and formation of structures similar to podosomes, lamellipodia and podonuts suggesting the role of this domain in actin re-organization. Also, HDAC6 ZnF UBP treatment caused increase in nuclear localization of ApoE and tubulin localization in microtubule organizing centre (MTOC). Therefore, our studies suggest the regulatory role of this domain in different aspects of neurodegenerative diseases. Upon HDAC6 ZnF UBP treatment, inactive phosphorylated form of GSK-3 beta increases without any change in total GSK-3 beta level. Conclusions: HDAC6 ZnF UBP was found to be involved in cytoskeletal re-organization by modulating actin dynamics and tubulin localization. Overall, our study suggests that ZnF domain of HDAC6 performs various regulatory functions apart from its classical function in aggresome formation in protein misfolding diseases.
Keywords: Actin; Cytoskeleton; HDAC6; Microtubule; neurodegeneration; Phosphorylation; Podonut; Podosomes; Tau; Tauopathies

Methylation as a key regulator of Tau aggregation and neuronal health in Alzheimer's disease - Balmik, Abhishek Ankur; Chinnathambi, Subashchandrabose (Cell Communication and Signaling, 2021)
Neurodegenerative diseases like Alzheimer's, Parkinson's and Huntington's disease involves abnormal aggregation and accumulation of toxic proteins aggregates. Post-translational modifications (PTMs) of the causative proteins play an important role in the etiology of disease as they could either slow down or accelerate the disease progression. Alzheimer disease is associated with the aggregation and accumulation of two major protein aggregates-intracellular neurofibrillary tangles made up of microtubule-associated protein Tau and extracellular Amyloid-beta plaques. Post-translational modifications are important for the regulation of Tau`s function but an imbalance in PTMs may lead to abnormal Tau function and aggregation. Tau methylation is one of the important PTM of Tau in its physiological state. However, the methylation signature on Tau lysine changes once it acquires pathological aggregated form. Tau methylation can compete with other PTMs such as acetylation and ubiquitination. The state of PTM at these sites determines the fate of Tau protein in terms of its function and stability. The global methylation in neurons, microglia and astrocytes are involved in multiple cellular functions involving their role in epigenetic regulation of gene expression via DNA methylation. Here, we have discussed the effect of methylation on Tau function in a site-specific manner and their cross-talk with other lysine modifications. We have also elaborated the role of methylation in epigenetic aspects and neurodegenerative conditions associated with the imbalance in methylation metabolism affecting global methylation state of cells.
Keywords: Aggregation; Epigenetics; methylation; Methyltransferases; post-translational modifications; Tau